The women of ISIS : gendered roles and agency under the caliphate - Mahmood, Sara (2017)
The study analyzes the role of women under the Islamic State of Iraq and Syria (ISIS), an extremist Islamist entity that according to popular opinion has denied women agency due to its patriarchal and gendered nature. The research redresses this misperception through asserting that women are imperative to ISIS, which in tum grants them agency. In order to establish this, the study incorporates Anthony Giddens' duality of structures, and Haleem's analysis of the ummah and the caliphate to explain the theoretical foundations for the emergence of gendered roles reinforced by ISIS. The research studies ISIS discourse to understand women's roles within the entity as, (i) mothers and wives, (ii) victims, and (iii) combatants and facilitators. Building on the roles conceptualized, the study reasons that women possess dual agency under ISIS. Firstly, agency emerges from internalization of the said roles and action based upon them, which ascertains the existence of the caliphate through strengthening the ummah. In this sense, women contribute to the ummah through procreation, indoctrination of the future generations with the values of the caliphate, and by complementing and bolstering the roles of the men as defenders of the ummah. Second, it argues that women possess agency under ISIS because they are seeking a legitimate authority, self-representation and self-governance within the caliphate similar to the men within their roles as the defenders of the ummah. In doing so, the study explains that despite the evident patriarchy and gendered construction of roles, women possess agency due to their criticality within ISIS' ummah and to the establishment of the caliphate.